PERLAKUAN AKUNTANSI ORGANISASI NIRLABA TERKAIT DENGAN PSAK NO. 45 TAHUN 2017 PADA GEREJA HKBP MARANATHA - Mulia Rahmah, SKom., M.Si.; Franky Bigky Munte (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This study aims to determine the application of financial accounting standards for non-profit entities, namely PSAK No. 45 in the process of recording accounting and financial statement presentation at HKBP Maranatha Church in Rawalumbu. This study uses a qualitative descriptive analysis method that can provide problem solving by collecting data, clarifying, analyzing and interpreting it, which records financial transactions in the HKBP Maranatha Church in Rawalumbu. Then the research of this problem will be compared with the existing standards, namely PSAK No. 45, so that it can provide a clear picture and can draw conclusions and suggestions arranged systematically. The results of the study indicate that the Foundation does not apply PSAK No. 45 in financial reporting. The HKBP Maranatha Rawalumbu Church in the accounting process only records cash income and cash disbursement. And the HKBP Maranatha Rawalumbu Church in its financial reporting has not applied the Financial Accounting Standards established by the Indonesian Institute of Accountants (IAI) based on PSAK No. 45 for non-profit entities. So that the financial statement presentation in HKBP MaranthaRawalumbu Church is not in accordance with PSAK No.45.